Emotion identification system through facial recognition using artificial intelligence - Paricela Canazas, Alexandra (2022)
The main objective of this paper is to develop a system to identify the emotions in a person using face recognition using artificial intelligence. The system development was based on the basic algorithm of Eigenfaces or Principal Component Analysis, one of the most widely used face recognition models. In addition, Python language and some of its available libraries such as Numpy, OpenCV y Sklearn were used for the implementation.